The advocacy for pedestrian safety study: cluster randomised trial evaluating a political advocacy approach to reduce pedestrian injuries in deprived communities. - Ronan A Lyons; Denise Kendrick; Elizabeth M L Towner; Carol Coupland; Mike Hayes; Nicola Christie; Judith Sleney; Sarah Jones; Richard Kimberlee; Sarah E Rodgers; Samantha Turner; Mariana Brussoni; et al. (PLoS ONE)
Objective To determine whether advocacy targeted at local politicians leads to action to reduce the risk of pedestrian injury in deprived areas. Design Cluster randomised controlled trial. Setting 239 electoral wards in 57 local authorities in England and Wales. Participants 617 elected local politicians. Interventions Intervention group politicians were provided with tailored information packs, including maps of casualty sites, numbers injured and a synopsis of effective interventions. Main outcome measures 25-30 months post intervention, primary outcomes included: electoral ward level: percentage of road traffic calmed; proportion with new interventions; school level: percentage with 20 mph zones, Safe Routes to School, pedestrian training or road safety education; politician level: percentage lobbying for safety measures. Secondary outcomes included politicians' interest and involvement in injury prevention, and facilitators and barriers to implementation. Results PRIMARY OUTCOMES DID NOT SIGNIFICANTLY DIFFER: % difference in traffic calming (0.07, 95%CI: -0.07 to 0.20); proportion of schools with 20 mph zones (RR 1.47, 95%CI: 0.93 to 2.32), Safe Routes to School (RR 1.34, 95%CI: 0.83 to 2.17), pedestrian training (RR 1.23, 95%CI: 0.95 to 1.61) or other safety education (RR 1.16, 95%CI: 0.97 to 1.39). Intervention group politicians reported greater interest in child injury prevention (RR 1.09, 95%CI 1.03 to 1.16), belief in potential to help prevent injuries (RR 1.36, 95%CI 1.16 to 1.61), particularly pedestrian safety (RR 1.55, 95%CI 1.19 to 2.03). 63% of intervention politicians reported supporting new pedestrian safety schemes. The majority found the advocacy information surprising, interesting, effectively presented, and could identify suitable local interventions. Conclusions This study demonstrates the feasibility of an innovative approach to translational public health by targeting local politicians in a randomised controlled trial. The intervention package was positively viewed and raised interest but changes in interventions were not statistically significance. Longer term supported advocacy may be needed. Trial registration Current Controlled Trials ISRCTN91381117.